(untitled) (Asian Journal of Agriculture, 2025)
Abstract. Gupta R, Tripathi J. 2025. A comparative study of electricity, irrigation and cropping pattern in three villages of Uttar Pradesh, India. Asian J Agric 9: 103-111. India’s economy, particularly Uttar Pradesh, one of its most agriculturally dependent states, heavily relies on agriculture. In the modern world, electricity plays a crucial role in every aspect of the economic and social life of the masses, and it became more vital in an agriculturist economy like India. Agriculture production and other agriculture-related activities have become increasingly dependent on the supply of electricity in recent times. Policymakers have expressed a strong desire to improve farming’s certainty and reliability with improved electricity supply and by reducing reliance on monsoons for irrigation. The present work highlights this issue by elucidating how the electricity supply influences agriculture production, investment in agriculture, employment structure, and the living standards of women within an economy or community. The present study, based on a comparison of three villages in Pratapgarh District, Uttar Pradesh, India, has explored several deeper questions associated with the impact of electrification on irrigation facilities, groundwater access, and cropping patterns. The study is mainly based on primary data that has been collected during the agricultural crop year 2019-2020. Major findings of the study indicate that villages with healthier electricity supplies had higher investment in irrigation, profitable cropping patterns, and reasonable water prices. Villages with a healthier electricity supply had a higher number of groundwater irrigation sources as well as two to three times more investment in irrigation facilities than villages with a poorer electricity supply. The healthier electricity supply also has a positive impact on the employment structure of the surveyed villages and the living conditions of women.